Frictional strength and fluidization of water-saturated kaolinite gouges at seismic slip velocities. (September 2021) - Kuo, Li-Wei; Wu, Wen-Jie; Kuo, Chia-Wei; Smith, Steven A.F.; Lin, Wei-Ting; Wu, Wei-Hsin; Huang, Yi-Hung
Abstract: Most previous experiments conducted on water-saturated clay-rich gouges sheared under extreme deformation conditions (including seismic slip rates e.g., 1 m/s, and displacements exceeding several meters) relied on gouge confinement using Polytetrafluoroethene (Teflon). Use of Teflon restricts such experiments to low normal stresses (≤2 MPa), which represents a significant limitation in our understanding of earthquake physics and seismic hazard assessment. To understand how normal stress and fluid affect the frictional behavior and deformation processes of clay-rich slipping zones, we performed rotary shear experiments using a purpose-built sample holder on water-saturated kaolinite gouges at a slip rate of 1 m/s and normal stresses ranging from 2 to 18 MPa. Results show that the apparent friction coefficient, μ, increases up to a peak value, μ p, of ~0.17–0.46, associated with marked gouge compaction. This is followed by dramatic weakening with increasing displacement to a steady-state value, μ ss, ~0.02–0.26 accompanied by gouge dilation. In-situ synchrotron X-ray diffraction and field-emission scanning electron microscopy show that clay aggregates within the gouge layer have a random fabric and do not experience mineral phase changes. On the basis of temperature measurements made during the experiments combined with a thermo-hydro-mechanical model, our results suggest that pore fluids within the gouge layer were mainly in liquid form during shearing. We conclude that dramatic weakening of kaolinite gouges at seismic rates under impermeable conditions is due to thermal pressurization, resulting in fluidization of the gouges. Our new experimental approach could be used to better understand earthquake physics and frictional processes of geological and civil interest. Highlights: Water-saturated kaolinite samples were frictionally investigated at seismic rates. A gouge sample holder was built to expand the experimental condition of normal stress. In impermeable condition, kaolinite has a dynamic weakening behavior during sliding. In addition, the presence of water inhibits the temperature rise in kaolinite. The weakening mechanism is thermal pressurization, resulting in fluidization of gouge.